Lithium-rich high-nickel porous positive electrode material as well as preparation method and application thereof

By designing lithium-rich high-nickel porous cathode materials, using some lithium ions to replace non-lithium metal cations, forming a layered crystal structure, and optimizing material performance through multiple heat treatments, the bottlenecks of existing high-nickel cathode materials in terms of gram capacity and cyclic performance are solved, and the goal of high-energy density lithium batteries is achieved.

CN119786591AActive Publication Date: 2025-04-08HUNAN CHANGYUAN LICO NEW ENERGY CO LTD +2

Patent Information

Application Number
CN202411736623.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-08
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Existing high-nickel cathode materials still have performance bottlenecks in meeting the high energy density of the strategic goal of 500Wh/kg lithium battery, especially in poor performance in gram capacity and cycle performance.

Method used

By designing a lithium-rich high-nickel porous cathode material, using the strategy of partial lithium ions to replace non-lithium metal cations, a unique lithium-rich phase layered crystal structure is formed, and the crystal structure and element distribution of the material are optimized through multiple heat treatments and the method of gradually introducing different element precursors.

Benefits of technology

The reversible specific capacity within the 0.1C current density and 2.5-4.35V voltage range is achieved to reach more than 249mAh/g, which significantly improves the rate performance and cycle life of the material, and meets the needs of high-energy-density lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786591A_ABST
    Figure CN119786591A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-rich high-nickel porous positive electrode material and a preparation method and application thereof. The positive electrode material is composed of Li, Ni, M, M ', M' 'and O elements. Wherein the molar ratio of the Ni element to the Li element is more than 0.64; the ratio of the total mole number of the elements Ni, M, M 'and M' 'to the mole number of the Li element is n, 0.7 lt; nlt; 1; m is selected from at least one of metal elements in the third period to the sixth period; m'is selected from at least one of metal elements in the second to fifth periods; m ''is selected from at least one of metal or non-metal elements and is different from M and M '; in an X-ray diffraction pattern of the positive electrode material obtained under CuKa radiation, at least one characteristic peak appears at 2 theta at 20-35 degrees; the positive electrode material is provided with a pore structure, and the pore structure comprises closed pores and open pores. The 0.1 C reversible specific capacity of the battery prepared from the positive electrode material can reach 249mAh / g or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a lithium-rich high-nickel porous positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous advancement of green energy technology and the popularization of the concept of carbon neutrality, the trend of electrification has gradually expanded from the traditional automotive industry to large-scale transportation fields such as aircraft and ships. Since 2023, many companies have proposed the strategic goal of increasing the energy density of lithium batteries to 500Wh / kg to meet the needs of these large tools for high energy storage. As a key component of lithium batteries, the performance of positive electrode materials directly determines the energy density of batteries. Therefore, the development of lithium battery positive electrode materials with higher specific energy has become a hot topic in current research.

[0003] Transition metal oxides, such as lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide and their derivatives, are considered to be strong candidates for high energy density cathode materials to achieve the strategic goal of 500Wh / kg lithium batteries due to their high theoretical working voltage and specific capacity. However, in practical applications, cathode materials are affected by multiple factors such as electrode-electrolyte side reactions, electron / ion transport barriers, and physical deformation stress, making it difficult to fully utilize their theoretical energy density.

[0004] In order to meet these challenges, researchers have optimized existing positive electrode materials and proposed lithium-rich manganese-based positive electrode materials and high-nickel positive electrode materials. For example, the lithium-rich manganese-based positive electrode materials disclosed in patent documents CN116856058A, CN115124089A, and CN116375110A have high capacity, but their operating voltage window is relatively high, and high voltage is required to trigger the reversible redox of lattice oxygen. Therefore, their upper limit of operating voltage reaches 4.6-4.8V, which exceeds the voltage tolerance window of existing commercial electrolyte systems. In addition, as the contribution of capacity gradually shifts from oxygen to transition metals, lithium-rich manganese-based positive electrode materials also have the problem of voltage attenuation.

[0005] Although the high-nickel cathode materials disclosed in patent documents CN116581280A, CN116799181A, and CN116588987A have a theoretical specific capacity of up to about 274mAh / g, and their actual capacity is closely related to the proportion of nickel and cobalt elements in the material, which is significantly lower than the theoretical specific capacity. And under the existing commercial electrolyte voltage tolerance window conditions (4.3-4.45V), the performance of high-nickel cathode materials still faces many challenges. For example, although the increase in nickel content can bring higher actual capacity, it is limited by the problems faced by the cathode materials. How to obtain a high-nickel cathode material with a specific capacity greater than 243mAh / g is still a key problem that needs to be solved urgently.

[0006] In order to break through this bottleneck, a variety of strategies have been proposed in the existing high-nickel technology. However, these strategies still have many shortcomings in practical applications. For example, the patent document CN116119737A adopts the method of improving the particle size distribution of the precursor to improve the material performance, but its gram capacity is 236mAh / g, which is significantly less than the target gram capacity; the patent document CN114914440A proposes to limit the half-peak width of the characteristic crystal plane diffraction peak of the high-nickel positive electrode material and reduce the proportion of non-stoichiometric products. The high-nickel positive electrode material 0.1C discharge specific capacity is about 236mAh / g at most; the patent document CN114551835A reduces the degree of nickel-nickel mixing by limiting the ratio between the characteristic peaks of the high-nickel positive electrode material, and the obtained high-nickel positive electrode material has a gram capacity of 235mAh / g under the condition of 0.1C current density. Therefore, the gram capacity of high-nickel positive electrode materials in the prior art is still at a relatively low level.

[0007] In summary, the preparation technology of high-nickel cathode materials to further maximize their capacity and improve their cycling performance, especially to meet the strategic goal of 500Wh / kg lithium batteries, still faces huge challenges and broad room for development. Summary of the invention

[0008] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a lithium-rich high-nickel positive electrode material, which has a high gram capacity.

[0009] The present invention also provides a method for preparing the positive electrode material.

[0010] The present invention also provides an application of the positive electrode material.

[0011] According to the positive electrode material of the first embodiment of the present invention, the positive electrode material is composed of Li, Ni, M, M', M", and O elements; wherein the molar ratio of Ni element to Li element is above 0.64; the ratio of the total molar number of Ni, M, M', M", elements to the molar number of Li element is n, 0.7 <n<1;

[0012] M is selected from at least one of the metal elements of periods 3 to 6;

[0013] M' is selected from at least one metal element of periods 2 to 5;

[0014] M" is selected from at least one of the metal or non-metal elements in periods 2 to 6, and is different from both M and M';

[0015] In the X-ray diffraction pattern (XRD) of the positive electrode material obtained under CuKa radiation, at least one characteristic peak appears at 2θ between 20° and 35°;

[0016] The positive electrode material has a pore structure, and the pore structure includes closed pores and open pores.

[0017] According to the positive electrode material of the embodiment of the present invention, at least the following beneficial effects are achieved: the battery made of the positive electrode material of the present invention has a reversible specific capacity of more than 249 mAh / g under the condition of 0.1C current density and 2.5-4.35V voltage range. The lithium-rich high-nickel porous positive electrode material of the present invention realizes the orderly arrangement of lithium ions in the non-lithium metal layer through the strategy of replacing non-lithium metal cations with some lithium ions, forming a unique lithium-rich layered crystal structure. In this structure, some lithium atoms not only replace the positions of some non-lithium metal atoms, but also form an ordered rather than mixed arrangement with non-lithium metal atoms. These lithium atoms located in the transition metal layer are also electrochemically active, not only contributing to capacity, but also providing additional support for lithium atoms in the lithium layer, limiting the escape of lattice oxygen. In addition, the doping of a variety of characteristic elements in the components further enhances the stability of the crystal structure and effectively anchors the lattice oxygen.

[0018] In the positive electrode material of the present invention, due to the periodic characteristics of the superlattice structure, one or more obvious diffraction characteristic peaks will appear in the region of 2θ angle range of 20° to 35° in the X-ray diffraction spectrum (XRD). The existence of these diffraction characteristic peaks not only verifies that the positive electrode material designed by the present invention has a unique crystal structure, but also provides strong evidence for its excellent electrochemical performance.

[0019] The pore structure in the scheme of the present invention provides more transmission channels for lithium ions in the electrolyte, shortening the diffusion path of ions inside the material. This design helps to speed up the insertion and deinsertion speed of lithium ions, thereby improving the charge and discharge rate and rate performance of the battery. At the same time, the pore structure helps to improve the thermal conductivity of the material, so that the heat generated by the battery during the charge and discharge process can be dissipated faster. This is of great significance for preventing battery overheating and improving the thermal stability and safety of the battery. The material morphology of the present invention innovatively combines closed-cell and open-cell designs. The open-cell structure greatly promotes the comprehensive infiltration of the electrolyte, can penetrate into the primary particles, and effectively reduces the migration distance (λ) of the ions. According to the formula of ion transmission time (τ) τ = λ2 / Di (Di represents the ion migration rate), it can be clearly known that the shortening of the migration distance can greatly reduce the ion transmission time, thereby significantly improving the rate performance of the material. At the same time, the carefully designed partial closed-cell structures in the material play a key role. They can effectively alleviate the deformation stress experienced by the particles during the battery charging and discharging process, thereby enhancing the structural stability of the material. Therefore, this combined design of open and closed pores not only ensures the reversible change of the crystal structure, but also effectively releases stress, which helps to maintain the stability of the material morphology.

[0020] According to some embodiments of the present invention, in the XRD spectrum of the positive electrode material, the peak intensity with the strongest signal in the characteristic peak in the region of 20° to 35° is recorded as A, and the peak intensity representing the (003) crystal plane is recorded as B, and the ratio of A to B satisfies:

[0021] According to some embodiments of the invention, 0.0001≤A / B≤0.05.

[0022] According to some embodiments of the invention, 0.0001≤A / B≤0.02.

[0023] According to some embodiments of the invention, 0.0001≤A / B≤0.01.

[0024] According to some embodiments of the invention, 0.004≤A / B≤0.01.

[0025] According to some embodiments of the present invention, the positive electrode material comprises a plurality of secondary particles consisting of primary particles.

[0026] According to some embodiments of the present invention, the closed pores are mainly distributed (more than 50%) inside the secondary particles.

[0027] According to some embodiments of the present invention, the closed cells are irregularly shaped.

[0028] According to some embodiments of the present invention, the maximum cross-sectional porosity of the secondary particles is 1% to 15%. The porosity within this horizontal range can alleviate the stress caused by volume change during charging and discharging to a certain extent, and help maintain the structural integrity of the positive electrode material. This is crucial for extending the cycle life of the battery and improving safety performance. In addition, the porosity within the horizontal range of the scheme of the present invention is conducive to the uniform penetration of the electrolyte in the positive electrode material, which helps to reduce the retention and drying of the electrolyte inside the material, thereby improving the cycle stability and consistency of the battery.

[0029] ​According to some embodiments of the present invention, the maximum cross-sectional porosity of the secondary particles is 5% to 10%.

[0030] According to some embodiments of the present invention, a single secondary particle of the positive electrode material comprises two or more crystallites, and a pore structure exists between adjacent crystallites.

[0031] According to some embodiments of the present invention, M and M' may be the same or different.

[0032] According to some embodiments of the present invention, M is selected from at least one of Co, Mn, Al, Zr, W, Nb, Sn, Sb, Ta, Sr, Y, Mg, Ti, La, Mo, and Mg.

[0033] According to some embodiments of the present invention, M is selected from at least one of Co, Mn, Mg, Sb, Mo, Nb, Al, Ti, Zr or W. According to some embodiments of the present invention, M' is selected from at least one of Al, Nb, Co, W, Mg, Li, Sn, Zr, Ti.

[0034] According to some embodiments of the present invention, the M' is selected from at least one of Nb, Co, W, Li, Sn, Zr, Al or Ti. According to some embodiments of the present invention, the M" is selected from at least one of Ti, Nb, P, Co, B, W, Li or Al. According to some embodiments of the present invention, the Ni / Li ratio in the positive material is above 0.7. For example, above 0.75, above 0.8, above 0.85, above 0.9, above 0.95, above 0.97, above 0.98, etc.

[0035] According to some embodiments of the invention, 0.75≤n≤0.99.

[0036] According to some embodiments of the invention, 0.8≤n≤0.99.

[0037] According to some embodiments of the invention, 0.9≤n≤0.99.

[0038] According to some embodiments of the present invention, the chemical formula of the positive electrode material is Li 1+x (Ni a M b M' c M” d ) 1-x O 2+α ; In the formula, 0 <x≤0.17;0.9≤a≤1;0≤b≤0.02;0≤c≤0.02;0≤d≤0.01;a+b+c+d=1;-0.05≤α≤0.05。

[0039] The cathode material of the present invention's solution is a nickel-rich high-nickel material. By appropriately increasing the content of lithium element and optimizing the utilization efficiency of non-lithium metal ions, while ensuring that the battery has high-capacity characteristics, a part of lithium ions can also be retained in the lithium layer lattice of the material. These retained lithium ions play a crucial role in maintaining the stability of the crystal structure. In addition, the present invention innovatively introduces a variety of doping elements, which can effectively anchor lattice oxygen and further enhance the stability of the lattice oxygen framework. Under the combined action of these comprehensive strategies, the cycle life of the cathode material of the present invention's solution has been significantly improved. The combination of high lithium content ratio and this unique combined design of open pores and closed pores further improves the actual reversible specific capacity of the high-nickel cathode material. The multi-level and multi-type pore distribution not only accelerates the transmission speed of lithium ions, but also effectively reduces the electrochemical polarization phenomenon and significantly improves the rate performance of the material. In the coin-type lithium battery test, this material exhibits a reversible specific capacity of more than 239 mAh / g in the current density range of 0.3C and the voltage range of 2.8 - 4.3V, reaching 98% of the specific capacity at the current density of 0.1C. In addition, when the voltage range is further broadened to 2.5 - 4.35V and tested at the current density of 0.1C, the reversible specific capacity can reach more than 249 mAh / g. This performance exceeds that of traditional high-nickel layered cathode materials, makes an important contribution to improving the energy density of lithium batteries, and promotes the development process of 500 Wh / kg high-energy-density lithium batteries.

[0040] Composition of high-nickel cathode material (Li 1+x (Ni a M b M’ c M” d ) 1-x O 2+α ), where the value of x is directly related to the number of available lithium ions in the composition and is a key factor in achieving high capacity. Specifically, the larger the value of x, the more available lithium ions in the material. In traditional high-nickel cathode materials, the molar ratio of lithium to non-lithium cations is usually 1:1, and the lithium ions exceeding this ratio are mostly attached to the surface of the cathode material in the form of lithium-containing impurities such as lithium carbonate and lithium hydroxide. In contrast, the present invention innovatively designs a composition with a ratio of lithium to transition metals greater than 1. The excess lithium ions not only exist inside the lattice of the cathode material but also play the roles of contributing capacity and supporting the crystal structure. Specifically, in the lithium-rich high-nickel cathode material of the present invention, the value range of x is limited to 0 < x ≤ 0.17, ensuring that the number of available lithium ions in its composition is increased compared with traditional materials.

[0041] In the process of pursuing high lithium ion utilization, traditional high-nickel layered positive electrode materials often face the problem of insufficient crystal structure support caused by limited lithium content, which easily causes the collapse of the crystal structure and reduces the cycle life. In response to this challenge, the present invention effectively solves the problems of traditional materials through ingenious structural design. Traditional high-nickel positive electrode materials adopt an α-NaFeO2 type crystal structure, in which lithium and non-lithium cations (such as transition metals such as Ni, Co, and Mn) occupy the 3b site to form a lithium layer and the 3a site to form a transition metal layer in a molar ratio of 1:1; however, the site exchange of trace lithium atoms and nickel atoms may lead to disordered lithium / nickel mixing, which has an adverse effect on material properties. In the scheme of the present invention, some lithium atoms replace the original positions of non-lithium metal atoms and form a unique structure of orderly arrangement of lithium and transition metals. Specifically, at the 3a position of the α-NaFeO2 type layered positive electrode material, lithium atoms and non-lithium metal atoms present a periodic arrangement, which breaks the traditional lithium-nickel mixing phenomenon and forms a structure with superlattice characteristics.

[0042] According to some embodiments of the present invention, 0.01≤x≤0.1, such as 0.02, 0.05, 0.07, 0.08, 0.1, etc.

[0043] According to some embodiments of the invention, 0.98≤a≤1.

[0044] According to some embodiments of the invention, 0.97≤a<0.995.

[0045] According to some embodiments of the present invention, 0.001≤b≤0.015, such as 0.002, 0.005, 0.007, 0.008, 0.01, 0.012, etc.

[0046] According to some embodiments of the present invention, 0.001≤c≤0.01, such as 0.002, 0.005, 0.007, 0.008, 0.01, 0.012, etc.

[0047] According to some embodiments of the present invention, 0.001≤d≤0.008, such as 0.002, 0.005, 0.007, etc.

[0048] The preparation method according to the second aspect of the present invention comprises the following steps:

[0049] S1, subjecting a mixture I containing a precursor and a lithium source to a heat treatment in an oxygen-containing atmosphere to form a sintered sample; wherein the precursor includes a Ni precursor material and an M element precursor material;

[0050] S2, mixing the primary sintered sample with an M' element precursor material to obtain a mixture II, and performing a secondary heat treatment on the mixture II in an oxygen-containing atmosphere to form a secondary sintered sample;

[0051] S3, mixing the secondary sintered sample with an M" element precursor material to obtain a mixture III, and performing a secondary heat treatment on the mixture III in an oxygen-containing atmosphere to obtain a positive electrode material;

[0052] Wherein, the Ni precursor material has a filamentous whisker morphology and a BET of 10m 2 / g or more; the oxygen intake in step S1 and step S2 independently satisfies the following relationship: 100≤(C / D)*T≤800; where C is the oxygen ventilation volume (m 3 / h), D is the weight of the heat treatment object (kg), and T is the heat treatment temperature (°C); the volume concentration of oxygen in the oxygen-containing atmosphere in steps S1, S2 and S3 is independently selected from 98% to 100%.

[0053] According to the preparation method of the embodiment of the present invention, at least the following beneficial effects are achieved: the preparation process of the scheme of the present invention can achieve fine control and optimization of the crystal structure, element distribution, performance and structural stability of the positive electrode material through step-by-step heat treatment and gradual introduction of different element precursors. This helps to improve the electrochemical performance, cycle life and safety performance of the battery, and provides a strong guarantee for the preparation of high-performance and long-life batteries. Through the preparation process of the scheme of the present invention, the positive electrode material is cleverly made to have closed-pore and open-pore morphology. This kind of closed pore inside the crystal helps to buffer the volume strain generated by the material during the process of lithium ion extraction and insertion, and improves the structural stability of the material; the open-pore morphology on the surface of the crystal helps the electrolyte to penetrate the pores, shorten the ion transmission path, and improve the rate performance of the material. According to the crystal growth principle and technology, the composition of the actual components of the crystal is related to the chemical reaction temperature and the component activation energy, and the component activation energy has a complex structure-activity relationship with the chemical potential in the raw material of the chemical reaction, the component concentration, etc.; the present invention unexpectedly found that after the oxygen intake meets the above conditions, a lithium-rich high-nickel porous positive electrode material with a superlattice can be obtained. The present invention innovatively uses a spherical nickel-containing precursor material with a high specific surface area. According to Wullf's theorem, crystal growth shows a trend of decreasing surface energy. Therefore, for the lithium-rich high-nickel porous positive electrode material in the present invention, a spherical nickel-containing precursor material with a high specific surface area is innovatively used. The spherical nickel-containing precursor material has a large specific surface area and high surface energy, which helps to form a morphological structure that combines closed pores and open pores.

[0054] According to some embodiments of the present invention, the Ni precursor material has at least one of the following characteristics: 1) BET range is 15-50m 2 / g; 2) the diameter range of the whiskers is preferably: 5-50nm; 3) the particle size Dv50 range of the Ni precursor material is 2-5μm; 4) the Ni precursor material component is selected from Ni(OH)2, Ni 0.97 Co 0.03 (OH)2 or Ni 0.98 Mn 0.01 Co 0.01 At least one of (OH)2.

[0055] The BET range of the nickel-containing precursor material of the present invention is 15-50m 2 / g, which reduces the cost of the production process and better ensures the sphericity and volume energy density. Filamentous whisker microcrystals with a diameter of less than 50nm are selected. Based on the capillary effect, h = (2σcosθ) / (ρgr), where h represents the height of the capillary liquid level, σ represents the surface tension, θ represents the contact angle, ρ represents the liquid density, g represents the acceleration of gravity, and r represents the radius of the capillary. Therefore, compared with traditional precursor materials, the precursor material with this structural feature has a stronger capillary effect, so that the precursor material containing lithium after liquefaction can fully adhere to any one or more precursor materials containing Ni and M, which helps the material lithiation reaction to be more uniform on the one hand, and helps the formation of lithium-rich structure on the other hand.

[0056] According to some embodiments of the present invention, the lithium source has at least one of the following characteristics: 1) the component is selected from at least one of LiOH or LiOH·H2O; 2) the particle size Dv50 ranges from 3 to 15 μm.

[0057] According to some embodiments of the present invention, the Ni precursor material includes Ni 0.97 Mn 0.005 Co 0.025 (OH)2、Ni 0.98 Mn 0.01 Co 0.01 At least one of (OH)2 or Ni(OH)2.

[0058] According to some embodiments of the present invention, at least one of the M element precursor material, the M' element precursor material, and the M" element precursor material contains an anionic group; the anionic group is selected from: 2- OH - WO4 2- 、AlO2 - 、ZrO3 2- 、Ti5O 12 4- PO4 3- 、C6H5O7 3- , C 36 H 70O4 2- 、CH3COO - 、HC2O4 - 、NbO3 2- At least one of .

[0059] According to some embodiments of the present invention, the M element precursor material is selected from ZrO2, Li2ZrO3, SrO, H2WO4, Nb(HC2O4)5, Li3PO4, LiAlO2, C 10 H5B 20 , MoO3·2H2O, WO3, SrCO3, SnO2, at least one of.

[0060] According to some embodiments of the present invention, the M' element precursor material is selected from at least one of CoOOH, Al(OH)3, Nb2O5·nH2O, MoO3·2H2O, H2WO4, Al2O3, LiOH, and TiO2.

[0061] According to some embodiments of the present invention, the M" element precursor material is selected from at least one of Li3NbO3, Al2O3, Li2WO4, TiO2, LiOH, LiOH·H2O, B2O3, H3BO3, Li3PO4, and H3PO4.

[0062] According to some embodiments of the present invention, the temperature of the highest temperature section of the primary heat treatment is 300-500° C.; and / or the treatment time of the highest temperature section is 5-15 hours.

[0063] According to some embodiments of the present invention, the total time of the primary heat treatment is 10 to 20 hours.

[0064] According to some embodiments of the present invention, the temperature of the highest temperature section of the secondary heat treatment is 500-720° C.; and / or the treatment time of the highest temperature section is 10-25 hours.

[0065] According to some embodiments of the present invention, the total time of the secondary heat treatment is 15 to 30 hours.

[0066] According to some embodiments of the present invention, the temperature of the highest temperature section of the three heat treatments is 280-600° C.; and / or the treatment time of the highest temperature section is 5-20 hours.

[0067] According to some embodiments of the present invention, the total time of the three heat treatments is 10 to 20 hours.

[0068] According to the application of the third aspect of the embodiment of the present invention, a lithium-ion battery comprises the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned preparation method.

[0069] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0071] Figure 1 Schematic diagram of the crystal structure of the particles constituting the positive electrode material according to an embodiment of the present invention.

[0072] Figure 2 Schematic diagram of the cross section of the positive electrode material particles according to an embodiment of the present invention.

[0073] Figure 3 This is a scanning electron microscope morphology image of the positive electrode material obtained in Example 1 of the present invention, magnified 20,000 times.

[0074] Figure 4 This is a scanning electron microscope morphology image of the positive electrode material obtained in Example 1 of the present invention, magnified 10,000 times (the scale length in the image is 5 μm).

[0075] Figure 5 This is a scanning electron microscope morphology image of the cross section of the positive electrode material particles obtained in Example 2 of the present invention, magnified 25,000 times.

[0076] Figure 6 This is a scanning electron microscope morphology image of the cross section of the positive electrode material particles obtained in Example 2 of the present invention, magnified 10,000 times.

[0077] Figure 7 This is the X-ray diffraction pattern of the positive electrode material particles obtained in Example 2 of the present invention.

[0078] Figure 8 for Figure 7 X-ray diffraction Figure 2 Partial magnification at an angle of 18-50°.

[0079] Fig. 9 This is a scanning electron microscope morphology image of the positive electrode material prepared in Comparative Example 1 of the present invention, magnified 20,000 times (the scale length in the image is 2 μm).

[0080] Fig.10 This is a scanning electron microscope morphology image of the positive electrode material prepared in Comparative Example 1 of the present invention, magnified 3000 times.

[0081] Fig.11 This is a charge and discharge specific capacity diagram of the positive electrode material prepared in Example 1 of the present invention at a 0.1C rate and a voltage range of 2.8-4.3V.

[0082] Fig.12This is a charge and discharge specific capacity diagram of the positive electrode material prepared in Example 1 of the present invention at a 0.1C rate and a voltage range of 2.5-4.35V.

[0083] Fig.13 This is a charge and discharge specific capacity diagram of the positive electrode material prepared in Example 1 of the present invention at a 0.3C rate and a voltage range of 2.8-4.3V.

[0084] Fig.14 1 is a cycle curve diagram of the positive electrode material of Example 1 of the present invention and Comparative Example 1.

[0085] Fig.15 This is an enlarged production diagram of the positive electrode material obtained in Example 3 of the present invention.

[0086] Description of reference numerals: 1. negative ion; 2. lithium ion (Li + ); 3. Other cations; 4. Closed-cell structure; 5. Open-cell structure. DETAILED DESCRIPTION

[0087] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0088] In the description of the present invention, the description with reference to the term "some embodiments" or the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0089] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0090] The equipment information used to characterize the positive electrode materials prepared in the examples and comparative examples of the present invention is as follows:

[0091] The high nickel layered cathode material for lithium-ion batteries was characterized using a scanning electron microscope (Hitachi SU8000).

[0092] The crystal structure of the high-nickel layered cathode material was analyzed using a powder X-ray diffractometer (Rigaku smartlab 3KW, Japan).

[0093] In the following embodiments, the volume concentration of oxygen in the oxygen-containing atmosphere is 99% (98% to 100%).

[0094] Example 1

[0095] In this example, a positive electrode material is prepared. The material is composed of Li, Ni, M, M', M'' and O elements, wherein M is Sr, Nb and Zr, M' is Co and Nb, and M'' is B, Ti and Nb.

[0096] The specific preparation process is as follows:

[0097] (1) Using a high-speed mixer, lithium hydroxide monohydrate used as a lithium source for lithium batteries, a precursor (nickel-containing precursor material (Ni 0.97 Mn 0.005 Co 0.025 (OH)2) and M precursor materials (strontium oxide, niobium oxalate, zirconium oxide)) are mixed uniformly to form a uniform mixture, wherein lithium hydroxide monohydrate and the precursor are mixed at a molar ratio of 1.02, wherein the lithium salt is concerned with the molar amount of Li, and the precursor is concerned with the molar amount of the transition metal (hereinafter referred to as T M ), so the above ratio can be expressed as: Li / T M =1.02, strontium oxide, niobium oxalate, and zirconium oxide are added according to the concentration ratio of cations in the positive electrode material. In this experiment, the concentrations of Sr, Nb, and Zr are 1000ppm, 3000ppm, and 4000ppm, respectively. The particle sizes (Dv50) of the nickel-containing precursor material and lithium hydroxide monohydrate are 3.5 and 11.6μm, respectively, and the specific surface area of ​​the nickel-containing precursor material is 25.2m 2 / g, and the average diameter of the whiskers on its surface is 30.5nm (Note: the whisker diameter value is obtained by using the software image, collecting 100 values ​​and taking the average value).

[0098] (2) In an oxygen-containing atmosphere furnace, the mixture obtained in step (1) is subjected to a heat treatment. The heat treatment conditions are: a heating rate of 3°C / min, a total heat treatment time of 15h, a maximum temperature of 500°C, and a maximum temperature treatment time of 10h. The weight of the heat-treated material is 20kg, and the ventilation flow rate is 20m / min. 3 / h.

[0099] (3) The once sintered sample of step 2 is mixed with a precursor material containing M' in the same manner as step 1, wherein the precursor material containing M' is a mixture of CoOOH and Nb2O5·nH2O, wherein the concentrations of Co and Nb are 6000 ppm and 2000 ppm, respectively.

[0100] (4) The mixture in step (3) is heat treated in an oxygen-containing atmosphere to form a secondary sintered sample. The heat treatment conditions are: a heating rate of 5°C / min, and a total heat treatment time of 16 hours. The highest temperature section temperature is 720°C, the heating rate is 5°C / min, and the highest temperature section treatment time is 11 hours. The weight of the heat-treated material is 20 kg, and the ventilation flow rate is 10 m / s. 3 / h.

[0101] (5) The secondary sintered sample in step (4) forms a uniform mixture with the precursor material containing M". The mixing method is the same as step 1, wherein the precursor material containing M" is a mixture of H3BO3, TiO2, and Al2O3, wherein the concentrations of B, Ti, and Al are 1000ppm, 1500ppm, and 1500ppm, respectively.

[0102] (6) The mixture in step (5) is heat treated in an oxygen-containing atmosphere to form a three-time sintered sample, thereby obtaining a lithium-rich high-nickel positive electrode material. The heat treatment conditions are: a heating rate of 5°C / min, and a total heat treatment time of 10h. The highest temperature section temperature is 400°C, the highest temperature section treatment time is 8h, and the heating rate is 5°C / min. The weight of the heat-treated material is 20kg, and the ventilation flow rate is 45m 3 / h.

[0103] The crystal structure diagram of the constituent particles of this material is shown in Figure 1 shown. Figure 1 The negative ion 1(O 2- ), occupying the 6c position; the lithium ion 2 (Li + ) mainly occupy the 3b position and partially occupy the 3a position; other cations besides lithium (such as Ni 2+ / Ni 3+ ,Co 3+ , Mn 4+ In other words, in the crystal structure of the constituent particles of the material of the embodiment of the present invention, the lithium ions occupy the 3a position in the layered crystal structure and form an orderly arrangement with the non-lithium cations in 3a to form a partial superlattice crystal structure.

[0104] The cross-sectional diagram of the particles of the material is shown in Figure 2 As shown. Figure 2It can be seen that the constituent particles of the scheme of the present invention have multi-type pore characteristics, and there are closed-pore structures 4 and open-pore structures 5 at the same time. Among them, the closed-pore structure 4 exists inside the particle, which is not connected to the outer surface, and the electrolyte cannot penetrate; while the open-pore structure 5 is connected to the outside world, and the electrolyte can directly contact the open pores.

[0105] The results of SEM characterization are as follows Figures 3-4 As shown. It can be seen from the figure that the material prepared in the embodiment of the present invention has a porous structure. According to XRD detection, the strongest peak among the characteristic peaks appearing at 20°~35°, its peak intensity is represented by A, the peak intensity representing the (003) crystal plane is B, the value of A / B is 0.0045, and the maximum cross-sectional porosity distribution of the particles is: 8.2%. Among them, the molar ratio of Ni element to Li element is 0.951, and the ratio of the total molar number of Ni, M, M', and M" elements to the molar number of Li element is 0.984.

[0106] Example 2

[0107] In this example, a positive electrode material was prepared. The preparation process was basically the same as that of Example 1, except that the Ni precursor material was Ni(OH)2, the concentration of Co in step (3) was 10000ppm, the temperature of the highest temperature section in step (4) was 665°C, the treatment time of the highest temperature section was 15h, and the total time of the secondary heat treatment was 20h. The positive electrode material prepared by the above operation was characterized by SEM. The SEM image of the cross section of the material particles is shown in FIG. Figures 5-6 As shown in the figure, it can be clearly seen that the material of the present invention has a closed-pore structure inside and an open-pore structure on the surface. The maximum cross-sectional porosity distribution of the particles is: 6.4%.

[0108] The XRD test results show that Figures 7-8 As shown in the figure, the strongest peak among the characteristic peaks appearing at 20°~35° is represented by A, the peak intensity representing the (003) crystal plane is represented by B, and the value of A / B is 0.0056. Among them, the molar ratio of Ni element to Li element is 0.980, and the ratio of the total molar number of Ni, M, M', M" elements to the molar number of Li element is 0.985.

[0109] Example 3

[0110] In this example, a positive electrode material is prepared, and its preparation process is basically the same as that of Example 1, except that: the lithium salt used in step (1) is LiOH, and niobium oxalate is replaced by WO3, and its concentration remains unchanged. Strontium oxide is replaced by LiAlO2, and its concentration remains unchanged. In step (5), Al2O3 is replaced by LiPO3, and LiOH is added, wherein the concentration of Li is 1000ppm. According to XRD detection, the strongest peak among the characteristic peaks appearing at 20°~35° has a peak intensity represented by A, and the peak intensity representing the (003) crystal plane is B. The value of A / B is 0.0051, and the maximum cross-sectional porosity distribution of the particles is: 7.1%. Among them, the molar ratio of Ni element to Li element is 0.948, and the ratio of the total molar number of Ni, M, M', and M" elements to the molar number of Li element is 0.981.

[0111] Example 4

[0112] In this example, a positive electrode material is prepared, and its preparation process is basically the same as that of Example 1, except that: the temperature of the highest temperature section of the heat treatment in step (2) is 300°C, the treatment time of the highest temperature section is 14h in total, and the total time of the first heat treatment is 19h. The temperature of the highest temperature section of the heat treatment in step (4) is 500°C, the treatment time of the highest temperature section is 23h in total, and the total time of the second heat treatment is 28h. The temperature of the highest temperature section of the heat treatment in step (6) is 700°C, the treatment time of the highest temperature section is 13h in total, and the total time of the third heat treatment is 18h. According to XRD detection, the strongest peak among the characteristic peaks appearing at 20° to 35°, its peak intensity is represented by A, the peak intensity representing the (003) crystal plane is B, the value of A / B is 0.0053, and the porosity distribution of the maximum cross-section of the particles is: 6.8%. The molar ratio of Ni element to Li element is 0.951, and the ratio of the total molar number of Ni, M, M', and M" elements to the molar number of Li element is 0.984.

[0113] Example 5

[0114] In this example, a positive electrode material is prepared, and its preparation process is basically the same as that of Example 1, except that: Li / T M =1.05, M precursor material is composed of H2WO4, Sb2O3, ZrO2, Nb2O5, wherein the concentrations of W, Sb, Zr, Nb are 2000ppm, 2000ppm, 3500ppm, 1000ppm respectively. According to XRD detection, the strongest peak among the characteristic peaks appearing at 20°~35° is represented by A, the peak intensity representing the (003) crystal plane is B, the value of A / B is 0.0063, and the maximum cross-sectional porosity distribution of the particles is 6.6%. Among them, the molar ratio of Ni element to Li element is 0.924, and the ratio of the total molar number of Ni, M, M', M" elements to the molar number of Li element is 0.956.

[0115] Example 6

[0116] In this example, a positive electrode material is prepared, and its preparation process is basically the same as that of Example 1, except that the Ni precursor material is replaced by Ni 0.98 Mn 0.01 Co 0.01 (OH)2, the lithium salt is replaced by LiOH, the Li / T M =1.1, the particle size Dv50 of the lithium salt is 6.3μm, the M material is composed of MoO3·2H2O, Sb2O3, ZrO2, Al2O3, wherein the concentrations of Mo, Sb, Zr, and Al are 8000ppm, 2000ppm, 3500ppm, and 500ppm, respectively. According to XRD detection, the strongest peak among the characteristic peaks appearing at 20°~35° is represented by A, the peak intensity representing the (003) crystal plane is B, the value of A / B is 0.0081, and the maximum cross-sectional porosity distribution of the particles is 5.9%. Among them, the molar ratio of Ni element to Li element is 0.891, and the ratio of the total molar number of Ni, M, M', and M" elements to the molar number of Li element is 0.913.

[0117] Example 7

[0118] In this example, a positive electrode material is prepared, and its preparation process is basically the same as that of Example 1, except that: Li / T M =1.03, M material is composed of WO3 and ZrO2, wherein the concentrations of W and Zr are 3000ppm and 2000ppm respectively; Co in M' is increased to 12000ppm, and LiOH is added, wherein the concentration of lithium is 500ppm, and the total treatment time in step (4) is 20h. According to XRD detection, the strongest peak among the characteristic peaks appearing at 20° to 35° is represented by A, and the peak intensity representing the (003) crystal plane is B, and the value of A / B is 0.0058. The maximum cross-sectional porosity distribution of the particles is 7.8%, wherein the molar ratio of Ni element to Li element is 0.950, and the ratio of the total molar number of Ni, M, M', and M" elements to the molar number of Li element is 0.984.

[0119] Example 8

[0120] In this example, a positive electrode material is prepared, and its preparation process is basically the same as that of Example 1, except that: Li / T M=1.07, M material is composed of MoO3·2H2O, Sb2O3, ZrO2, SrCO3, wherein the concentrations of Mo, Sb, Zr, Sr are 3000ppm, 2000ppm, 3500ppm, 500ppm respectively. M” adds Li2WO4, wherein the concentration of W is 1000ppm. According to XRD detection, the strongest peak among the characteristic peaks appearing at 20°~35°, its peak intensity is represented by A, the peak intensity representing the (003) crystal plane is B, the value of A / B is 0.0075, and the maximum cross-sectional porosity distribution of the particles is 6.3%, wherein the molar ratio of Ni element to Li element is 0.904, and the ratio of the total molar number of Ni, M, M', M” elements to the molar number of Li element is 0.940.

[0121] Example 9

[0122] In this example, a positive electrode material was prepared. The preparation process was basically the same as that in Example 1, except that the weight of the heat-treated material in step (2) was 10 kg and the ventilation flow rate was 6 m / s. 3 / h, the weight of the heat-treated material in step (4) is 5kg, and the ventilation flow rate is 5m 3 / h. According to XRD detection, the strongest peak among the characteristic peaks appearing at 20°~35° is represented by A, the peak intensity representing the (003) crystal plane is represented by B, the value of A / B is 0.0048, and the maximum cross-sectional porosity distribution of the particles is: 7.6%. Among them, the molar ratio of Ni element to Li element is 0.951, and the ratio of the total molar number of Ni, M, M', M" elements to the molar number of Li element is 0.984.

[0123] Example 10

[0124] In this example, a positive electrode material was prepared. The preparation process was basically the same as that in Example 1, except that: Li / TM = 1.1, the precursor was replaced by Ni(OH)2, the weight of the heat-treated material in step (2) was 10 kg, and the ventilation flow rate was 5 m 3 / h, the highest temperature section temperature is 420℃, the highest temperature section treatment time is 15h in total, and the total heat treatment time is 20h. Step (4) The weight of the heat-treated material is 5kg, and the ventilation flow rate is 6m 3 / h, the highest temperature section temperature is 650℃, the highest temperature section treatment time is 18h in total, and the total secondary heat treatment time is 23h. According to XRD detection, the strongest peak among the characteristic peaks appearing at 20°~35°, its peak intensity is represented by A, the peak intensity representing the (003) crystal plane is B, the value of A / B is 0.0083, and the maximum cross-sectional porosity distribution of the particles is: 9.1%. Among them, the molar ratio of Ni element to Li element is 0.909, and the ratio of the total molar number of Ni, M, M', and M" elements to the molar number of Li element is 0.913.

[0125] Comparative Example 1

[0126] In this example, a positive electrode material was prepared. The preparation process was basically the same as that in Example 1, except that the precursor particles were densely packed and the specific surface area of ​​the precursor was 5 m 2 / g, the obtained comparative example positive electrode material.

[0127] The SEM images of the prepared materials are shown in Figures 9-10 As shown in the figure, it can be seen that there are no obvious holes on the surface. In addition, it can be seen from its cross-sectional view that there are no obvious pores inside. And in the X-ray diffraction pattern (XRD) of the positive electrode material obtained under CuKa radiation, no characteristic peak appears at 2θ at 20°~35°. Among them, the molar ratio of Ni element to Li element is 0.951, and the ratio of the total molar number of Ni, M, M', and M" elements to the molar number of Li element is 0.984.

[0128] Comparative Example 2

[0129] In this example, a positive electrode material was prepared. The preparation process was basically the same as that of Example 1, except that in step (2), the mixture obtained in step (1) was subjected to a first heat treatment in an oxygen-containing atmosphere furnace. The heat treatment conditions were: the highest temperature section temperature was 720°C, and the highest temperature section treatment time was 10 hours. The weight of the heat-treated material was 20 kg, and the ventilation flow rate was 1 m 3 / h. In the XRD diffraction pattern of the obtained positive electrode material under CuKa radiation, no obvious peak appeared in the 2θ range of 20° to 35°. Among them, the molar ratio of Ni element to Li element was 0.951, and the ratio of the total molar number of Ni, M, M', and M" elements to the molar number of Li element was 0.984.

[0130] Comparative Example 3

[0131] In this example, a positive electrode material is prepared, and its preparation process is basically the same as that of comparative example 1, with the only difference being that in step (1), lithium hydroxide monohydrate and the precursor are mixed at a molar ratio of 1.4. In the XRD diffraction pattern of the obtained positive electrode material under CuKa radiation, multiple diffraction peaks appear at 2θ at 20°~35°, and the A / B value is 0.012. Similarly, there are no obvious holes on the surface of the positive electrode material particles. Among them, the molar ratio of Ni element to Li element is 0.693, and the ratio of the total molar number of Ni, M, M', and M" elements to the molar number of Li element is 0.717.

[0132] Performance Testing

[0133] The positive electrode material prepared in the above embodiments and comparative examples was mixed with the conductive agent carbon black and the binder polyvinylidene fluoride in a mass ratio of 90:5:5, and the solvent N-methyl-2-pyrrolidone (NMP) was added to form a slurry (the mass proportion of the solvent was 16wt%±1%), and the slurry was evenly applied to the carbon-coated aluminum foil current collector to obtain a positive electrode membrane. A metal lithium sheet was used as the negative electrode, a polypropylene microporous membrane (Celgard2400) was used as a separator, and 1 mol / LLiPF6 (the solvent was a mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) in a volume ratio of 1:1:1) was used as an electrolyte, and the 2430 button batteries were assembled in an argon-protected glove box.

[0134] The assembled battery was tested on a Blue Electric charge and discharge tester with a constant current charge and discharge test at a temperature of 25°C and at 0.1C (equivalent to 20mAg -1 ) rate. Among them, the 2430 button battery assembled with the high nickel layered positive electrode material prepared in Example 1 has a charge and discharge curve at different rates and different voltage ranges as shown in FIG. Fig.11 , Fig.12 , Fig.13 As shown, the cycle curves of the button cells obtained by assembling the materials of Example 1 and Comparative Example 1 are as follows: Fig.14 The high nickel layered positive electrode materials prepared in other embodiments and comparative examples of the present invention were assembled into lithium batteries according to the above method, and their electrochemical performance was tested. The results are shown in Table 1.

[0135] Table 1

[0136]

[0137]

[0138] From the data in Table 1, it can be seen that the lithium-rich high-nickel porous positive electrode material prepared according to the embodiment of the present invention has higher discharge specific capacity, rate performance and cycle stability, which is significantly superior to the comparative example. This shows that the present solution is significantly progressive. Figure 3 , Figure 4 , Figure 5 , Figure 6 The morphological characteristics of the present invention have been verified. Figure 8 for Figure 7 The local area magnification features and their characteristic peaks verify the structural characteristics of the lithium-rich and high-nickel porous positive electrode material in the present invention. Fig.15 This is an optical photograph of the positive electrode material in Example 3 produced in an industrial sagger, indicating that the scheme of the present invention is suitable for large-scale production of high-nickel layered positive electrode materials and has high commercial value.

[0139] In the solution of the present invention, in the first heat treatment (S1), an oxygen-containing atmosphere is introduced into the mixture of the precursor (containing Ni element and M element) and the lithium source to form a primary sintered sample. This process helps to initially form the required crystal structure and promotes the chemical reaction between lithium element and the elements in the precursor, laying a good foundation for the subsequent steps. In the second step (S2) and the third step (S3), the M' precursor material and the M” precursor material are respectively introduced, and after being mixed with the sintered sample of the previous step, a secondary heat treatment is carried out. This method of gradually adding different element precursors can achieve fine control of the element distribution in the cathode material, optimize the distribution state of elements such as lithium and transition metals (such as Ni, M, M', M”) in the material, thereby improving the electrochemical performance and structural stability of the material. Through multiple heat treatments, the chemical reaction inside the material and the perfection of the crystal structure can be further promoted, and the crystallinity and density of the material can be improved. This helps to enhance the ion conduction performance and electron conduction performance of the material, thereby increasing the charge and discharge rate and energy density of the battery. Multiple heat treatments can also reduce the defects and stresses inside the material to a certain extent and enhance the structural stability of the material. This is of great significance for extending the cycle life of the battery and improving the safety performance. The preparation process is carried out in steps, and each step can be independently optimized and controlled for process parameters. This helps to achieve precise control and optimization of the performance of the cathode material and improve the quality and consistency of the product.

[0140] The chemical formula of the cathode material is Li 1+x (Ni a M b M’ c M” d ) 1-x O 2+α ; where 0 < x < 0.17; 0.9 ≤ a ≤ 1; 0 ≤ b ≤ 0.02; 0 ≤ c ≤ 0.02; 0 ≤ d ≤ 0.01; a + b + c + d = 1; -0.05 ≤ α ≤ 0.05, where α is used to balance the valence. The valence of oxygen is -2, the valence of Li is +1, and the valence of the remaining transition metals is +N (depending on the actual transition metals), where Ni ions exist in +2 and +3 valence states (assuming the content of +3 valence Ni is y). The valence balance relationship is as follows: 1 + x + (a×(2×(1 - y) + 3×y) + M×b + c×M' + d×M”)×(1 - X) = 2×(2 + α). The non-zero value of α has no obvious change on the overall effect.

[0141] The above has made a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Within the knowledge scope of those of ordinary skill in the art, various changes can be made without departing from the purpose of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material is composed of Li, Ni, M, M', M'' and O elements; wherein the molar ratio of Ni element to Li element is above 0.64; the ratio of the total molar number of Ni, M, M', M'' elements to the molar number of Li element is n, 0.7 <n<1; M is selected from at least one of the metal elements of periods 3 to 6; M' is selected from at least one metal element of the 2nd to 5th periods; M" is selected from at least one of the metal or non-metal elements in periods 2 to 6, and is different from both M and M'; In the X-ray diffraction spectrum of the positive electrode material obtained under CuKa radiation, at least one characteristic peak appears at 2θ between 20° and 35°; The positive electrode material has a pore structure, and the pore structure includes closed pores and open pores.

2. A positive electrode material according to claim 1, characterized in that: In the XRD spectrum of the positive electrode material, the peak intensity with the strongest signal in the characteristic peak in the region of 20° to 35° is recorded as A, and the peak intensity representing the (003) crystal plane is recorded as B. The ratio of A to B satisfies:

0. The positive electrode material comprises a plurality of secondary particles composed of primary particles, and the maximum cross-sectional porosity of the secondary particles is 1% to 15%; preferably, the maximum cross-sectional porosity of the secondary particles is 5% to 10%.

3. A positive electrode material according to claim 1, characterized in that: M is selected from at least one of Co, Mn, Al, Zr, W, Nb, Sn, Sb, Ta, Sr, Y, Mg, Ti, La, Mo or Mg; and / or, M' is selected from at least one of Al, Nb, Co, W, Mg, Li, Sn, Zr or Ti; and / or, the M" is selected from at least one of Ti, Nb, P, Co, B, W, Li or Al.

4. A positive electrode material according to claim 1, characterized in that: The steps include:

5. A positive electrode material according to any one of claims 1 to 4, characterized in that: The chemical formula of the positive electrode material is Li 1+x (Ni a M b M' c M” d ) 1-x O 2+α ; In the formula, 0 <x≤0.17;0.9≤a≤1;0≤b≤0.02;0≤c≤0.02;0≤d≤0.01;a+b+c+d=1;-0.05≤α≤0.05。 6. A method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: S1, subjecting a mixture I containing a precursor and a lithium source to a heat treatment in an oxygen-containing atmosphere to form a sintered sample; wherein the precursor includes a Ni precursor material and an M element precursor material; S2, mixing the primary sintered sample with an M' element precursor material to obtain a mixture II, and performing a secondary heat treatment on the mixture II in an oxygen-containing atmosphere to form a secondary sintered sample; S3, mixing the secondary sintered sample with an M" element precursor material to obtain a mixture III, and performing a secondary heat treatment on the mixture III in an oxygen-containing atmosphere to obtain a positive electrode material; The lithium source has at least one of the following characteristics: 1) the component is selected from at least one of LiOH or LiOH·H2O; 2) the particle size Dv50 ranges from 3 to 15 μm. Wherein, the Ni precursor material has a filamentous whisker morphology and a BET of 10m 2 / g or more; the oxygen intake in step S1 and step S2 independently satisfies the following relationship: 100≤(C / D)*T≤800; where C is the oxygen ventilation volume (m 3 / h), D is the weight of the heat treatment object (kg), T is the heat treatment temperature in the highest temperature section (°C); the volume concentration of oxygen in the oxygen-containing atmosphere in steps S1, S2 and S3 is independently selected from 98% to 100%.

7. The preparation method according to claim 6, characterized in that: The Ni precursor material has at least one of the following characteristics: 1) BET range is 15-50m 2 / g; 2) the diameter range of the whiskers is preferably: 5-50nm; 3) the particle size Dv50 range of the Ni precursor material is 2-5μm; 4) the Ni precursor material component is selected from Ni(OH)2, Ni 0.97 Co 0.03 (OH)2 or Ni 0.98 Mn 0.01 Co 0.01 At least one of (OH)2.

8. The preparation method according to claim 6, characterized in that: The preparation method satisfies at least one of the following conditions:

9. The preparation method according to claim 6, characterized in that: At least one of the M element precursor material, the M' element precursor material, and the M" element precursor material contains an anion group; the anion group is selected from: 2- OH - WO4 2- 、AlO2 - 、ZrO3 2- 、Ti5O 12 4- PO4 3- 、C6H5O7 3- , C 36 H 70 O4 2- 、CH3COO - 、HC2O4 - 、NbO3 2- At least one of .

10. The preparation method according to any one of claims 6 to 9, characterized in that: 1) The temperature of the highest temperature section of the primary heat treatment is 300-500° C.; and / or, the treatment time of the highest temperature section is 5-15 hours; 2) The temperature of the highest temperature section of the secondary heat treatment is 500-720°C; and / or, the treatment time of the highest temperature section is 10-25 hours; ​ 3) The temperature of the highest temperature section of the three heat treatments is 280-600° C.; and / or the treatment time of the highest temperature section is 5-20 hours.

11. A lithium ion battery, characterized in that: The invention comprises the positive electrode material as claimed in any one of claims 1 to 5 or the positive electrode material prepared by the preparation method as claimed in any one of claims 6 to 10.

Citation Information

Patent Citations

  • Ultrahigh-nickel quaternary positive electrode material as well as preparation method and application thereof

    CN114551835A

  • Ultrahigh-nickel polycrystalline nickel-aluminum-magnesium lithium zirconate positive electrode material as well as preparation method and application thereof

    CN114914440A

  • Manganese-rich precursor material, lithium-rich manganese-based positive electrode material, preparation methods thereof and lithium ion battery

    CN115124089A

  • Precursor of ternary positive electrode material and preparation method thereof

    CN116119737A

  • Lithium-rich manganese-based positive electrode material and preparation method and application thereof

    CN116375110A

Cited By

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN120453366A